2020
DOI: 10.29045/14784726.2020.12.5.3.31
|View full text |Cite
|
Sign up to set email alerts
|

The use of simulation as a teaching modality for paramedic education: a scoping review

Abstract: <sec id="s1">Background: Simulation is a broad concept used as an education pedagogy for a wide range of disciplines. The use of simulation to educate paramedics is a frequently used but untested modality to teach psycho-motor skills, acquire new knowledge and gain competence in practice. This review identifies how simulation is currently being used for the education of paramedics, and establish the context for future application. </sec> <sec id="s2">Methods: A scoping review of the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
1
12
0
2
Order By: Relevance
“…An exposure to simulations and real clinical advocacy issues during training would arm and equip them with adequate knowledge on health advocacy in practice. 45 A study in Ghana by Dadzie, Aziato 29 reported that being empathetic, nurturing, ethical, assertive, persistent and compassionate are keys to advocating. This is contrary to what our participants reported, as they held that clients had to be considerate for nurses to advocate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exposure to simulations and real clinical advocacy issues during training would arm and equip them with adequate knowledge on health advocacy in practice. 45 A study in Ghana by Dadzie, Aziato 29 reported that being empathetic, nurturing, ethical, assertive, persistent and compassionate are keys to advocating. This is contrary to what our participants reported, as they held that clients had to be considerate for nurses to advocate.…”
Section: Discussionmentioning
confidence: 99%
“…An exposure to simulations and real clinical advocacy issues during training would arm and equip them with adequate knowledge on health advocacy in practice. 45…”
Section: Discussionmentioning
confidence: 99%
“…Kemudian dengan penelitian Okamoto, Gouda, Koide, Tokimasa, Kageyama, Iwamoto, Shiomi, Kusano, Tanaka, Kiya, Tada, & Koetaka (2020), dan Wheeler & Dippenaar (2020) mengungkapkan bahwa pembelajaran melalui simulasi memberikan pengalaman dan kesempatan belajar pada peserta didik untuk mempraktekkan sesuatu. Meskipun demikian, konteks temuan penelitian ini sedikit berbeda dengan konteks temuan penelitian Okamoto, Gouda, Koide, Tokimasa, Kageyama, Iwamoto, Shiomi, Kusano, Tanaka, Kiya, Tada, & Koetaka (2020) dan Wheeler & Dippenaar (2020). Pada penelitian Okamoto, Gouda, Koide, Tokimasa, Kageyama, Iwamoto, Shiomi, Kusano, Tanaka, Kiya, Tada, & Koetaka (2020) lebih mengarah kepada pengembangan program pembelajaran simulasi, sehingga dapat meningkatkan kekuatan komunitas.…”
Section: Hasil Dan Pembahasan 31 Hasilunclassified
“…Pada penelitian Okamoto, Gouda, Koide, Tokimasa, Kageyama, Iwamoto, Shiomi, Kusano, Tanaka, Kiya, Tada, & Koetaka (2020) lebih mengarah kepada pengembangan program pembelajaran simulasi, sehingga dapat meningkatkan kekuatan komunitas. Penelitian Wheeler & Dippenaar (2020) mengarah pada modalitas pengajaran utama dalam mendidik dan melatih keterampilan psikomotorik paramedis dengan menggunakan teknik yang berbeda.…”
Section: Hasil Dan Pembahasan 31 Hasilunclassified
“…Prehospital environments for research and training have typically been “staged” using live simulation, where participants complete scenarios using highly realistic physical tools and technology-enhanced manikins (Abelsson et al, 2014; McKenna et al, 2015). However, live simulation requires considerable resources, is difficult to replicate precisely, and requires facilitators and participants to be at the same location (Mills et al, 2020; Wheeler & Dippenaar, 2020). Computer-based virtual simulation and virtual reality simulation use virtually created environments, which can overcome some of these limitations (Birtill et al, 2021; Foronda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%